A narrative review of diabetic bone disease: Characteristics, pathogenesis, and treatment - Wu, Bo; Fu, Zhaoyu; Wang, Xinyu; Zhou, Pengcheng; Yang, Qifan; Jiang, Ye; Zhu, Dong (Frontiers in Endocrinology, 2022)
Recently, the increasing prevalence of diabetes has made it a major chronic illness which poses a substantial threat to human health. The frequency of osteoporosis among patients with diabetes has grown considerably. Diabetic osteoporosis is a secondary osteoporosis induced by diabetes. Patients with diabetic osteoporosis exhibit variable degrees of bone loss, low bone mineral density, bone microarchitecture degradation, and increased bone fragility with continued diabetes, increasing their risk of fracture and impairing their ability to heal after fractures. At present, there is extensive research interest in diabetic osteoporosis and many significant outcomes have been reported. However, a systematic and comprehensive review is still lacking. This review elaborates on diabetic osteoporosis in the aspects of characteristics, pathogenesis, and treatment. A novel bioinformatics analysis was also performed, and ten hub genes of diabetic osteoporosis were screened, wherein the PI3K-Akt signaling pathway was identified as a promising treatment target.